Code Mixing in Cooking Terms on Jesselyn MCI 8’S Tiktok Account in Gourmet with Jess Segment - Yulianti, Fitri; Dadan Firdaus; Toneng Listiani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the phenomena of English–Indonesian code mixing in Jesselyn Lauwreen's short-form video material, specifically in her Gourmet With Jess TikTok series. Lauwreen is the winner of MasterChef Indonesia Season 8. The research distinguishes and classifies three linguistic forms—intra-sentential code mixing, intra-lexical code mixing, and code mixing involving pronunciation change—based on Charlotte Hoffman's (1991) typology of code mixing. In order to investigate how English cooking terminology is incorporated into Indonesian narratives, 10 TikTok videos were examined using a qualitative descriptive technique. The results show that the most common technique is intra-sentential code mixing, in which English phrases like "Now aku bakal steam" or "Chinese stir fry beef dengan sayur-sayuran" are included into Indonesian sentence structures to promote conceptual clarity and linguistic flexibility. Additionally common is intra-lexical code mixing, which is demonstrated by hybrid constructions such as "di-marinate," "garnish-nya," and "shred gitu," which show Jesselyn's adaptive linguistic innovation by fusing local grammar conventions with international culinary language. The least common type of code mixing was a change in pronunciation, but it was noticeable in cases like "chicken stock," which is pronounced using Indonesian phonology. This indicates localized accessibility without compromising professional authority. The study emphasizes that code mixing on TikTok is a purposeful decision influenced by audience expectations, platform affordances, and the creation of culinary identities rather than just being a linguistic need. In addition to providing insights into how multilingual influencers use language to negotiate cultural capital, relatability, and expertise in Indonesia's developing digital culinary realm, these findings validate the usefulness of Hoffman's methodology in evaluating multimodal digital discourse.